The Relationship Between Emotional Intelligence and Organizational Commitment to Hotel Staff - Kurniawaty Kurniawaty; Akhmad Syarifuddin; Nurfatwa Andriani Yasin (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Commitment is a person's loyalty to the organization. A committed person always intends to continue working with the organization and is committed to achieving its goals, whereas emotional intelligence as a form of social intelligence that allows employees to manage their own emotions and distinguish them from the emotions of others. This study aims to examine the effect of emotional intelligence on organizational commitment in 100 hotel staff in Kab.Bone, South Sulawesi by using the cillation analysis method. This study found that there was a positive but not significant influence between emotional intelligence on affective commitment, and there was a positive and significant influence between emotional intelligence on ongoing commitment and normative commitment on hotel staff. These findings suggest that the tendency that hotel staff who have high emotional intelligence is not inclined towards strong affective commitment, whereas in the formation of ongoing commitment and normative commitment hotel staff give the impression that they have higher levels of emotional intelligence tend to want to develop good working relationships, are very tolerant when faced with work pressures, Able to respond to all conditions with good emotions without losing patience.